An investigation of the promotion effects of uncertain level discount: evidence from China. Issue 4 (9th September 2019) - Tan, Hongying; Akram, Umair; Sui, Yujia
Abstract : Purpose: Uncertain level discount (ULD) is a type of promotion combining regular discount (RD) with uncertainty. The purpose of this paper is to explore the impact of ULD on consumers' perceived quality compared with RD and to identify the relevant influencing mechanism and boundary for the effectiveness of ULD. Design/methodology/approach: Three online experiments were conducted with 445 participants from China. First, experiment 1 compares the attractiveness of ULD and RD. Second, experiment 2 evaluates the impacts of ULD and RD on consumers' perceived quality and clarifies the mechanism in this process. Finally, experiment 3 examines the moderating effect of product knowledge. Findings: ULD has the same level of attractiveness as RD with equivalent expected discount value for consumers. Besides, consumers in ULD give higher ratings to product quality compared with those in RD, and the lower diagnosticity of price cues in ULD underlies the differential effects of ULD vs RD. Furthermore, product knowledge moderates the relationship between the two promotions and perceived quality. Practical implications: The findings provide valuable guidance for managers to conduct promotional campaigns. ULD is an effective promotion to attract consumers to purchase with keeping consumers' perceived quality high, and such effectiveness will rise for products that consumers are unfamiliar with. Managers can make rational use of ULD to achieve positive promotion results in both the short and long term. Originality/value: Few studies pay attention to the long-term effects of the uncertain promotion. This research profoundly investigates the impact of ULD on perceived quality, which complements existing studies from a more integrated perspective that combines short- and long-term effects. Also, this research identifies the mechanism based on the cue diagnosticity theory and puts forward a new explanation for positive uncertainty in uncertain promotions. Finally, this research applies the impact of product knowledge on information process strategies into the uncertain promotion, which clarifies the utility boundary of ULD from a new perspective and offers a more comprehensive understanding for this promotion.